Analyze Marketing Strategies to Improve Competitiveness of MSMES iN Bandar Lampung City - Oktasa, Muhatir; Narundana, Vonny Tiara (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This research aims to: (1) produce interactive multimedia learning based on Google Site that is suitable for use in teaching and learning. (2) Produce practical and easy-to-learn interactive multimedia learning based on Google Site. (3) Determine the effectiveness of interactive multimedia based on Google Site. This research is a Research and Development (R&D) study using the ADDIE model. The study was conducted on 10th-grade students of State Islamic Senior High School 1 in Langkat. The method used in this model is Quasi-Experimental. The research sample consisted of 72 students, with 36 students as the experimental group taught using interactive multimedia based on Google Site and 36 students as the control group taught using picture media. The results of the study prove that there is a significant difference between the English learning outcomes of students taught using interactive multimedia based on Google Site and those taught using picture media. This is indicated by the obtained data, where the significance value obtained is 0.003. The significance value (sig) < 0.05, thus is rejected and is accepted. Therefore, it can be concluded that interactive multimedia based on Google Site is better than picture media.